2018
DOI: 10.1088/1361-6463/aaa692
|View full text |Cite
|
Sign up to set email alerts
|

Significant contribution from impurity-band transport to the room temperature conductivity of silicon-doped AlGaN

Abstract: Silicon-doped n-type (0 0 0 1) AlGaN materials with 60% and 85% AlN content were studied close to the doping condition that gives the lowest resistivity (Si/III ratios in the ranges 2.8-34 × 10 −5 and 1.3-6.6 × 10 −5 , respectively). Temperature-dependent conductivity and Hall-effect measurements showed that, apart from the diffusion-like transport in the conduction band, a significant amount of the conductivity was due to phonon-assisted hopping among localized states in the impurity band, which became almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…1. [9][10][11][12][13][14][28][29][30][31][32][33][34][35][36] The lowest resistance of n-AlGaN with an AlN mole fraction of 62% was achieved in this study. The lowest resistivity value of the Al 0.62 Ga 0.38 N layer reached 6.6 × 10 −3 Ω cm at the Si concentration of 3.2 × 10 19 cm −3 .…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…1. [9][10][11][12][13][14][28][29][30][31][32][33][34][35][36] The lowest resistance of n-AlGaN with an AlN mole fraction of 62% was achieved in this study. The lowest resistivity value of the Al 0.62 Ga 0.38 N layer reached 6.6 × 10 −3 Ω cm at the Si concentration of 3.2 × 10 19 cm −3 .…”
mentioning
confidence: 86%
“…(Color online) Resistivity values as a function of the AlN mole fraction for n-AlGaN layers. The data reported from other studies are indicated as open symbols,[9][10][11][12][13][14][28][29][30][31][32][33][34][35][36] while our results are shown as red closed symbols.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Figure 8 plots the calculated Si concentrations against the disilane to group III ratios (Si 2 H 6 /III ratios) (Dinh et al, 2016 a , 2016 b ; Pampili et al, 2018). In MOCVD growth, the group III atoms are introduced via metal precursors in the form of organic compounds such as trimethylgallium and trimethylaluminium, while ammonia is the nitrogen source.…”
Section: Resultsmentioning
confidence: 99%
“…These Al x Ga 1- x N samples included polar-oriented [0001] (samples AP, BP, CP) and semipolar-oriented layers [112-2] (samples ASP, CSP). More details on the growth of the Al x Ga 1– x N:Si layers from the Tyndall Institute are given elsewhere (Li et al, 2013; Dinh et al, 2016 a , 2016 b ; Pampili et al, 2018; Spasevski et al, 2021). Samples labeled TS are Al x Ga 1– x N layers with various AlN contents and crystal polarities grown at Technische Universität Berlin (Knauer et al, 2013; Kusch et al, 2014; Mehnke et al, 2016; Foronda et al, 2020).…”
Section: Methodsmentioning
confidence: 99%